De la zarzuela a la ciencia ficción: El anacronópete, de Enrique Gaspar. Expansión de los límites de lo fantástico en la coyuntura del nacionalismo - Brina, Maximiliano (Studia Romanica Posnaniensia, 2018)
This article addresses Enrique Gaspar’s novel El anacronópete (1887) by means of the articulation of the fantastic genre and nationalism. The nineteenth century witnessed a powerful scientific and technological development, which introduced economic, political and social changes. This can be traced in literature, especially in the second half of the century: for example, in the antagonistic positions between Emilio Ferrari and Gaspar Núñez de Arce in the field of poetry, or novels by Benito Pérez Galdós as Doña Perfecta (1876), in which the tension between the countryside and the city is compared to that existing between tradition and modernity. In this context, the value of Gaspar's novel surpasses the anecdote of presenting the first time machine in literature, eight years before Wells’s. Its value lies in the way in which, starting from the articulation of scientific and literary discourse, it expands the limits of the fantastic while using the procedure to address the question of national identity. The action takes place during the International Exhibition in Paris in 1878. The novel shows the popularity of the “famous Jules Verne” in Spain, whose “marvelous hypotheses” will be considered “children's toys in the face of the magnitude of the real invention of the modest Zaragoza neighbour of Spain”. More than a science fiction novel, the text calls for the incorporation of concepts related to the process of creation of national identities from such disciplines as history and sociology.